2015
DOI: 10.1108/qrfm-09-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Internet banking and customer satisfaction in Pakistan

Abstract: This study determines the effects of service quality dimensions on customer satisfaction in Pakistan by using SERVQUAL model. A survey research questionnaire of 30 items has been adopted and collects the data of 400 respondents from the users of internet banking of different bank located in Karachi city of Pakistan. Reliability analysis shows that all dimensions are reliable. Results of factor analysis confirm the grouping of adopted questioner. At last, regression analysis indicates significant positive relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 19 publications
4
97
1
3
Order By: Relevance
“…It mediates overall satisfaction, which is an antecedent of loyalty (Levy and Hino, 2016). Jun and Palacios (2016) study mobile banking service quality in USA, while Amin (2016) and Raza et al (2015) study internet banking service quality and its relationship to customer satisfaction and loyalty in Saudi Arabia and Pakistan, respectively. The authors found that service quality significantly impacts on satisfaction and consequently leads to loyalty.…”
Section: Research Hypotheses Developmentmentioning
confidence: 99%
“…It mediates overall satisfaction, which is an antecedent of loyalty (Levy and Hino, 2016). Jun and Palacios (2016) study mobile banking service quality in USA, while Amin (2016) and Raza et al (2015) study internet banking service quality and its relationship to customer satisfaction and loyalty in Saudi Arabia and Pakistan, respectively. The authors found that service quality significantly impacts on satisfaction and consequently leads to loyalty.…”
Section: Research Hypotheses Developmentmentioning
confidence: 99%
“…The analysis indicates a significant positive relationship between assurance, tangibility, reliability and responsiveness with customer satisfaction (Raza et al, 2015). Conversely, empathy shows a positive but insignificant effect on the customer satisfaction.…”
Section: The Literature Review Of E-banking Service Quality Measuremementioning
confidence: 89%
“…Munusamy et al (2010) investigated five dimensions: assurance, reliability, tangibles, empathy, and responsiveness in the Malaysian banking industry and was unable to provide evidence of association with customer satisfaction except for tangibles. The insignificance effect of empathy was later confirmed by Raza et al (2015). However, Siddiqi (2011) provided evidence of the effects of service quality attribute on customer satisfaction, including empathy and tangibility.…”
Section: A Review Of the Relevant Literaturementioning
confidence: 93%